Management of schneiderian papilloma with midfacial degloving - Farhat dr (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Schneiderian Papilloma is a rare and benign sinonasal tumor. The symptoms include unilateral nasal obstruction, epistaxis, nasal drainage, bilateral nasal obstruction, nasal mass and sinusitis. The exact location, extension and the histological evaluation of the tumour is very important in order to decide the surgical modality. Here, we are reporting a case of Schneiderian Papilloma of the left nasal cavity and left maxillary sinus in a 62 years old man managed with midfacial degloving.Keywords : schneiderian papilloma; midfacial degloving